Clinical features and prognosis of parotid metastasis of breast cancer: retrospective analysis of 57 cases - Guo, Fengli; Fu, Honghai; Wang, Yuhua; Hua, Yitong; Wang, Xiaohong; Zhang, Yingzhe (Frontiers in Oncology, 2024)
PurposeParotid gland metastases originating from breast origin are extremely rare, with their clinical presentation, therapeutic approaches, and prognostic indicators remaining to be elucidate.MethodsA comprehensive retrospective review was conducted, analyzing the clinical characteristics and prognostic factors of 57 patients diagnosed with parotid metastasis of breast cancer in the existing literature. Notably, our study included two unique cases of patients who developed contralateral and ipsilateral parotid metastases, occurring 5 years and 32 years respectively after primary surgery. This analysis aimed to provide a deeper understanding of the disease presentation and identify potential prognostic indicators.ResultsThe primary clinical manifestation presented in breast cancer patients with parotid metastases was painless masses in the parotid glands, synchronously or metachronously occurred with primary breast tumors. The predominant pathological subtype among these patients was invasive ductal carcinoma. Out of the 57 patients studied, 24 (42.1%) exhibited metastases solely in the ipsilateral parotid gland, while 18 cases (31.6%) involved either the contralateral or bilateral parotid gland. Patients may solely exhibit metastasis in the parotid gland, or they may present with concurrent multiple metastases in other organs. Patients who suffered from parotid metastases, either merely or accompanied with bone-only metastasis, exhibited significantly longer overall survival (OS) rates compared to those who had concomitant metastases in other organs (1.23 ± 0.26 years vs 4.46 ± 0.77 years, P=0.046). While no statistically significant differences in OS were observed among patients presenting with metastases in the ipsilateral, contralateral, or bilateral parotid glands, a notable variance could be discerned from the Kaplan-Meier curve analysis. Additionally, no significant difference in survival was exhibited between patients with different interval of progression from primary breast sites to initial diagnosis of parotid metastases (uDF), nor for patients who were treated with surgery or palliative therapy.ConclusionParotid metastasis, a rare and distinctive form of breast cancer metastasis, demands particular scrutiny in patients exhibiting metastasis to multiple organs or contralateral or bilateral parotid glands.